The Old English Account of the Seven Heavens - VOLMERING, NICOLE (Celtic Studies Publications, 2014)
Edition and translation, with introduction and notes, of the Seven Heaven section in the composite Old English homily on Doomsday in Cambridge, Corpus Christi College (CCCC) 41, pp 287–95, the relevant section being on pp 292–5.
The End and Beyond: Medieval Irish Eschatology
Keywords: Old English; Seven Heavens; Apocrypha; Eschatology